2021
DOI: 10.1038/s41467-021-21516-6
|View full text |Cite|
|
Sign up to set email alerts
|

The secreted endoribonuclease ENDU-2 from the soma protects germline immortality in C. elegans

Abstract: Multicellular organisms coordinate tissue specific responses to environmental information via both cell-autonomous and non-autonomous mechanisms. In addition to secreted ligands, recent reports implicated release of small RNAs in regulating gene expression across tissue boundaries. Here, we show that the conserved poly-U specific endoribonuclease ENDU-2 in C. elegans is secreted from the soma and taken-up by the germline to ensure germline immortality at elevated temperature. ENDU-2 binds to mature mRNAs and n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 36 publications
(33 reference statements)
1
20
1
Order By: Relevance
“…ENDOU was also reported to regulate c-Myc expression, cell proliferation and nucleotide metabolism via fine-tuning of mRNA stability in tumor cells (40,41,70,71). The previously indicated selective cytotoxicity of ENDOU against tumor cells (39,40,81,82) and its deregulation in cervical carcinogenesis observed in the present study may indicate the potential benefits of its pharmacological modulation in patients with cervical carcinoma. Similarly, the results of the present study demonstrated that cervical tumors with low ENDOU expression were characterized by the molecular phenotype associated with poorer differentiation, as well as perturbation in certain pathways, including transcriptional regulation in cancer, growth factor and kinase signaling.…”
Section: Discussionsupporting
confidence: 73%
“…ENDOU was also reported to regulate c-Myc expression, cell proliferation and nucleotide metabolism via fine-tuning of mRNA stability in tumor cells (40,41,70,71). The previously indicated selective cytotoxicity of ENDOU against tumor cells (39,40,81,82) and its deregulation in cervical carcinogenesis observed in the present study may indicate the potential benefits of its pharmacological modulation in patients with cervical carcinoma. Similarly, the results of the present study demonstrated that cervical tumors with low ENDOU expression were characterized by the molecular phenotype associated with poorer differentiation, as well as perturbation in certain pathways, including transcriptional regulation in cancer, growth factor and kinase signaling.…”
Section: Discussionsupporting
confidence: 73%
“…Here we outline our recent findings about protection and maintenance of germline immortality by the soma via secretion of the endoribonuclease ENDU-2 in C. elegans. [8] We found that ENDU-2 binds to mRNA and affects abundance of transcripts in -both soma and germline. Based on these findings we propose that ENDU-2 confers a non-cell-autonomous mechanism to control gene expression across tissue boundaries, thus mediating soma-to-germline communication.…”
Section: Introductionmentioning
confidence: 73%
“…33) In the report by Qi et al, endu-2 is mainly expressed in intestinal cells. 33) Then, the secreted RNase ENDU-2 from intestinal cells may non-autonomously affects ADL thermosensitivity.…”
Section: Adl Thermosensory Neurons Involved In Cold Tolerancementioning
confidence: 98%
“… 30 ) Qi et al recently noted that RNase ENDU-2 behaves as a secretory protein, and that the secretion signal peptide comprised of the first 19 amino acids in ENDU-2 is essential for this phenomenon. 33 ) Although the detailed molecular machinery involved in ENDU-2 secretion, such as packaging in exosomes or lysosomes, is unclear, ENDU-2 has been shown to be taken up by tissues other than the expressing cells. 33 ) In the report by Qi et al , endu-2 is mainly expressed in intestinal cells.…”
Section: Adl Thermosensory Neurons Involved In Cold Tolerancementioning
confidence: 99%
See 1 more Smart Citation